RANCANG BANGUN SISTEM OTOMATIS PEMANTAU PERTUMBUHAN BALITA BERBASIS MIKROKONTROLER - Wahyu, Sandy Tri; Rasmana, Susijanto Tri; Triwidyastuti, Yosefine (Journal of Control and Network Systems (JCONES), 2017)
Abstract: Nutrient is principal to the health of the toddler. When the nutrient is not fulfilled or exceed of limits, the toddler will have some trouble of healty. Health of toddler can be seen from process grow up. All this time growth monitoring of toddler using method and tools in manual, from measurement of weight and height are done in manual mode using conventional tool. By reviewing issues on top, we intend to make automatic monitoring system of toddler growth based on microcontroller. In this research, system for monitoring based on microcontroller aims to be implemented in hospital, children’s clinic, and other health center. Keyword :Toddler, SRF05,Mikcrocontroller, Loadcell